Species richness, new reports and inventory update of bat assemblage of the Gorgona National Natural Park, Colombia - Murillo G., Oscar E.; Bedoya, M. Juliana; Velandia-Perilla, Jorge H.; Yusti-Muñoz, Ana P. (Revista de Biología Tropical, 2014)
The information resulting from inventories is crucial for tracking the effects of habitat alteration and climate change on biodiversity, and for determining conservation priorities. Bats provide several ecosystem services and reflect the status of the populations they interact with. However, the inventory of bats in Gorgona National Natural Park can be incomplete since relatively few intensive surveys have been done. Using mist nets in areas with different forest cover, 670 bats representing 10 species and three families (Emballonuridae, Phyllostomidae and Vespertilionidae) were captured. Frugivorous species were more abundant in the survey, but a higher number of insectivorous species were registered. A model that incorporates detectability suggests that 33 bat species occur (95% credible interval=[26,39]) and that frugivorous species have a higher detectability than other trophic guilds. To the 13 bat species reported for Gorgona, we added two: Peropteryx macrotisand Mimon crenulatum. In conclusion, our results add two new records of bats to Gorgona, and suggest that the inventory of bats in Gorgona is incomplete, and aerial insectivorous bats have been underrepresented because of the exclusive use of mist nets. Rev. Biol. Trop. 62 (Suppl. 1): 407-417. Epub 2014 February 01.